Peran Kepemimpinan Transformasional dalam Meningkatkan Employee Engagement Karyawan di Era Digital pada Perusahaan Retail Ranch Market - Jaceline Sumargo; Lusy Rahmawati; Stevanus Giral Santoso; Tan Evan Tandiyono; Gustaf Naufan Febrianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid development of digital technology has transformed the way organizations conduct business activities and manage human resources. These changes require organizations to have employees who are not only competent but also possess a high level of employee engagement to adapt effectively to the dynamic work environment. This study aims to analyze the role of transformational leadership in enhancing employee engagement among employees of Ranch Market in the digital era. Transformational leadership is regarded as a leadership style that inspires, motivates, and encourages employees to develop their potential through a clear vision, effective communication, and individualized consideration. This research employed a quantitative approach by collecting data through questionnaires distributed to Ranch Market employees. Data analysis was conducted to examine the relationship between transformational leadership dimensions and employee engagement, which includes vigor, dedication, and employee involvement in their work. The findings indicate that transformational leadership plays a positive and significant role in improving employee engagement. Leaders who are able to inspire, build trust, encourage innovation, and support employee development have been proven to strengthen employees’ attachment to the organization. Furthermore, transformational leadership fosters a supportive and adaptive work environment, enabling employees to respond effectively to technological changes and evolving work systems. The results suggest that the implementation of transformational leadership can serve as an effective strategy for organizations in addressing the challenges of the digital era while promoting productivity, employee commitment, and sustainable organizational performance. Therefore, transformational leadership remains a crucial factor in maintaining a highly engaged workforce and achieving long-term competitive advantage.